La morfologia verbale del milanese antico di Bonvesin dra Riva - Domokos, György (Verbum – Analecta Neolatina, 2007)
Bonvesin dra Riva was the most important author of Milan in the late Middle Ages. His works are partly in Latin and partly in medieval Milanese volgare. The goal of the present paper is to offer a complete scheme of verbal morphology of his language.